Optimalisasi Pengarsipan Surat Masuk dan Surat Keluar dengan Sistem Berbasis Web Kantor Desa Waharia - Gunawan Prayitno; Merlin Tandi Pakila (STMIK Pesat Nabire, 2024)
Management of incoming and outgoing mail archives is a crucial aspect of organizational administration, including at the Waharia Village Office. Currently, the archiving process is still done manually, posing various challenges such as lengthy search times, risks of document damage or loss, and the need for extensive storage space. To address these issues, this research developed a web-based mail archiving information system. The study findings indicate that the web-based archiving system enhances the efficiency and effectiveness of archive management by enabling quick and easy recording, storage, and retrieval of mail archives. Documents can be accessed from anywhere with an internet connection, equipped with advanced search features to expedite the retrieval process. Furthermore, the use of digital storage reduces the risks of document damage or loss, while controlled access management enhances data security.